Computational fluid dynamics in the numerical simulation analysis of end-to-side anastomosis for coarctation of the aorta - Yang, Fang; Zhai, Bo; Hou, Li-Gong; Zhang, Qian; Wang, Jie (Journal of Thoracic Disease, 2018)
Background: Based on CT image data, a computational fluid dynamics (CFD) model of the aortic arch was established. We aimed to investigate the hemodynamic features associated with end-to-side anastomosis (ESA) surgery for coarctation of the aorta (CoA) by CFD model. Methods: The data of enhanced CT two-dimensional medical images obtained through clinical practice were processed using medical image post-processing software. The three-dimensional model of the aortic arch was obtained through the geometric model and boundary condition. This was subsequently transformed into a CAD model, which can be used for simulation calculation. Results: The CFD model accurately reflected the shape of the aortic arch, and produced the hemodynamic results before and after ESA for CoA. Conclusions: The CFD model provides a virtual execution platform for the scientific research of aortic arch disease and will be helpful to evaluate the operation plan, even to determine the best surgical procedure. Hemodynamic analysis may be helpful to evaluate the therapeutic effects of other aortic diseases.